A possible mechanism of hyperlipidemia in a patient with metastatic non-small cell lung cancer on lorlatinib therapy. (December 2021) - McGee, Katherine; Stone, Neil J; Wadhwani, Shikha; Kanwar, Yashpal S; Villaflor, Victoria; Akhter, Nausheen
Introduction: We report the case of a woman who developed hyperlipidemia on lorlatinib therapy found to have minimal change disease. We review therapies for cancer known to alter the lipid profile, in addition to reviewing secondary hyperlipidemia workup. We also propose a mechanism for lorlatinib-induced hyperlipidemia. Case report: A 63 year old woman with non-small cell lung adenocarcinoma on lorlatinib therapy develops marked hyperlipidemia. Management & outcome: A secondary hyperlipidemia workup is performed which reveals nephrotic range proteinuria. Minimal change disease is found on renal biopsy. The hyperlipidemia was initially responsive to statin therapy, then required addition of ezetimibe. Discussion: This is a case of hyperlipidemia in a patient on lorlatinib. The case highlights that therapies for lung cancer and other malignancies have the potential to alter the lipid profile. We propose minimal change disease as a possible mechanism for lorlatinib-induced dyslipidemia. Additionally, we discuss the crucial aspects of secondary hyperlipidemia workup.